A Novel N-terminal Region to Chromodomain in CHD7 is Required for the Efficient Remodeling Activity. Issue 18 (3rd September 2021) - Lee, Eunhye; Kang, Chanshin; Purhonen, Pasi; Hebert, Hans; Bouazoune, Karim; Hohng, Sungchul; Song, Ji-Joon
Graphical abstract: Highlights: An N-terminal to Chromodomain (N-CRD) of CHD7 is identified as a novel nucleosome binding module. N-CRD contains a high-conserved arginine stretch, a reminiscent of arginine anchor for interacting the acidic patch. The acidic patch is required for CHD7 to bind and remodel nucleosomes. N-CRD is required for the efficient remodeling activity of CHD7. Abstract: Chromodomain-Helicase DNA binding protein 7 (CHD7) is an ATP dependent chromatin remodeler involved in maintaining open chromatin structure. Mutations of CHD7 gene causes multiple developmental disorders, notably CHARGE syndrome. However, there is not much known about the molecular mechanism by which CHD7 remodels nucleosomes. Here, we performed biochemical and biophysical analysis on CHD7 chromatin remodeler and uncover that N-terminal to the Chromodomain (N-CRD) interacts with nucleosome and contains a high conserved arginine stretch, which is reminiscent of arginine anchor. Importantly, this region is required for efficient ATPase stimulation and nucleosome remodeling activity of CHD7. Furthermore, smFRET analysis shows the mutations in the N-CRD causes the defects in remodeling activity. Collectively, our results uncover the functional importance of a previously unidentified N-terminal region in CHD7 and implicate that the multiple domains in chromatin remodelers are involved in regulating their activities.